Dietary Trichosporon mycotoxinivoron modulates ochratoxin-A induced altered performance, hepatic and renal antioxidant capacity and tissue injury in broiler chickens. (25th September 2021) - Bhatti, Sheraz Ahmed; Khan, Muhammad Zargham; Saleemi, Muhammad Kashif; Hassan, Zahoor Ul
Abstract: Ochratoxin A (OTA), an important fungal metabolite in foods and feeds has been shown to induce oxidative stress and cellular injuries to human and animal subjects. This study was designed to investigate the mode of action of a biological modifier Trichosporon mycotoxinivorans (TM), against OTA-mediated oxidative stress and tissue toxicity on broiler chickens. The birds were offered diets supplemented with OTA (0.15 and 0.3 mg/kg feed) and/or TM (0.5, 1.0 g/kg) for 42 days of age, and blood and tissue samples were collected to examine the oxidative stress, biochemical and histopathological parameters. Dietary OTA at all the tested levels induced the hepatic and renal tissue injury as indicated by significant decreased total antioxidant capacity in these organs along with significant decreased ( p  ≤ 0.05) serum concentrations of total proteins and albumin. The serum concentrations of alanine aminotransferase (ALT) and urea were significantly increased, and these observations were further supported by degenerative changes and increased relative weights of liver and kidneys. The dietary supplementation of TM at both tested levels relieved the detrimental impact of 0.15 and 0.3 mg OTA/kg on the studied parameters. The results of the study demonstrated that dietary TM significantly protects broiler chickens by reducing OTA-induced oxidative damage and tissue injury. Highlights: Ochratoxin A (OTA) intoxication results in oxidative stress and tissue damage. Dietary Trichosporon mycotoxinivorans (TM) attenuates the negative impact of OTA. TM supplementation boosts the total antioxidant capacity (TAC) of liver and kidney. Dietary TM significantly ameliorates OTA induced tissue damage.